Reformulasi Ekstradisi terhadap Kejahatan Lintas Batas Negara di Era Globalisasi (Studi Kasus Warga Negara Rakyat Republik Tiongkok dengan Taiwan) - Yusuf Muhamad Said; Muannas Alaidid; Misbahul Huda; Dian Priheryanti Havid (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Indonesia's extradition laws, particularly Law No. 1 of 1979, face challenges in the globalization era, especially with cross-border crimes involving citizens from China and Taiwan. The current civil law and administrative procedure system allows for significant government subjectivity, unlike common law systems that prioritize due process and judicial decisions, where individuals can refuse extradition. This was evident in Indonesia's rejection of Taiwanese citizens' extradition to China and Hendra Rahardja's refusal from Australia, highlighting the need to curb politically motivated or unjust refusals. Therefore, reform of Extradition Law No. 1 of 1979, specifically Article 14, is crucial. This reform should enhance legal certainty, reduce subjectivity, and uphold national sovereignty and justice principles. It must also embrace a "living law" concept, aligning with societal values and ensuring practical benefits. Furthermore, Indonesia should actively champion an ASEAN extradition convention with common standards, particularly for sophisticated cybercrime, drawing inspiration from the European Union's model.